Gamification- and Virtual Reality-Based Learning Environment for UML Class Diagram Modeling - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Bassanelli, Simone; Engels, Gregor (IEEE Global Engineering Education Conference 2024)

Effects of Human Avatar Representation in Virtual Reality on Inter-Brain Connections - Yigitbas, Enes; Kaltschmidt, Christian (Proceedings of the 8th International Conference on Artificial Intelligence and Virtual Reality (AIVR’24))

Interaction Techniques for Remote Maintenance in an AR Shared Environment - Krings, Sarah Claudia; Biermeier, Kai; Yigitbas, Enes (Proceedings of the 10th International Working Conference on Human-Centered Software Engineering (HCSE'24))

An Exploratory Study of Fear-Inducing Factors in Virtual Reality Experiences - Leichtweiß, Justus; Yigitbas, Enes (Proceedings of the 12th International Conference on Serious Games and Applications for Health (SeGAH'24))

Prototyping Cross-Reality Escape Rooms - Krois, Sebastian; Yigitbas, Enes (Proceedings of the 10th International Working Conference on Human-Centered Software Engineering (HCSE'24))

Einfluss der periodischen Struktur auf geführte Wellen in gewebeverstärkten Polymeren - Claes, Leander (Fortschritte der Akustik - DAGA 2024)

Authenticité et patrimoine culturel. Genèse et adoption du critère d‘authenticité par la Convention du Patrimoine mondia - Seng, Eva- Maria (Nouvelles lectures patrimoniales. Le Pays de la Loire au miroir de l’Europe)

Developing a VR Factory Walkthrough for Use in Schools - Krings, Sarah Claudia; Yigitbas, Enes; Sauer, Stefan (Proceedings of the 10th International Working Conference on Human-Centered Software Engineering (HCSE'24))

Common pitfalls to avoid while using multiobjective optimization in machine learning - Akhter, Junaid; Fährmann, Paul David; Sonntag, Konstantin; Peitz, Sebastian (arXiv)

Symbol-Specific Sparsification of Interprocedural Distributive Environment Problems - Karakaya, Kadiray; Bodden, Eric (Proceedings of the IEEE/ACM 46th International Conference on Software Engineering)
Previous work has shown that one can often greatly speed up static analysis by computing data flows not for every edge in the program’s control-flow graph but instead only along definition-use chains. This yields a so-called sparse static analysis. Recent work on SparseDroid has shown that specifically taint analysis can be “sparsified” with extraordinary effectiveness because the taint state of one variable does not depend on those of others. This allows one to soundly omit more flow-function computations than in the general case. In this work, we now assess whether this result carries over to the more generic setting of so-called Interprocedural Distributive Environment (IDE) problems. Opposed to taint analysis, IDE comprises distributive problems with large or even infinitely broad domains, such as typestate analysis or linear constant propagation. Specifically, this paper presents Sparse IDE, a framework that realizes sparsification for any static analysis that fits the IDE framework. We implement Sparse IDE in SparseHeros, as an extension to the popular Heros IDE solver, and evaluate its performance on real-world Java libraries by comparing it to the baseline IDE algorithm. To this end, we design, implement and evaluate a linear constant propagation analysis client on top of SparseHeros. Our experiments show that, although IDE analyses can only be sparsified with respect to symbols and not (numeric) values, Sparse IDE can nonetheless yield significantly lower runtimes and often also memory consumptions compared to the original IDE.

Schulleitungen als Promotoren. Unterstützung digitalisierungsbezogener Schulentwicklungsprozesse durch Schulleitungen und deren Wahrnehmung durch Lehrpersonen. - Gerick, Julia; Kieseler, Janine; Herrmann, Daniel; Eickelmann, Birgit (MedienPädagogik (Occasional Papers))

Erinnerung als Formproblem. Feridun Zaimoglus Versuche, deutsche Geschichte ‚zu schreiben‘: „Führer“ (2021) und „Bewältigung“ (2022) - Eke, Norbert (Feridun Zaimoglu. Kasseler Grimm-Poetikprofessur 2023)

Zwischen Herrschaft und Utopie . Eine theologische Reflexion über die ambivalente Mensch-Tier-Beziehung - Herdramm, Henrike (Laudato)
Keywords: Tiertheologie; Tierethik; Psalm 104; Mensch-Tier-Beziehung

Detecting Security-Relevant Methods using Multi-label Machine Learning - Johnson, Oshando; Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (Proceedings of the 46th International Conference on Software Engineering, IDE Workshop)
To detect security vulnerabilities, static analysis tools need to be configured with security-relevant methods. Current approaches can automatically identify such methods using binary relevance machine learning approaches. However, they ignore dependencies among security-relevant methods, over-generalize and perform poorly in practice. Additionally, users have to nevertheless manually configure static analysis tools using the detected methods. Based on feedback from users and our observations, the excessive manual steps can often be tedious, error-prone and counter-intuitive. In this paper, we present Dev-Assist, an IntelliJ IDEA plugin that detects security-relevant methods using a multi-label machine learning approach that considers dependencies among labels. The plugin can automatically generate configurations for static analysis tools, run the static analysis, and show the results in IntelliJ IDEA. Our experiments reveal that Dev-Assist's machine learning approach has a higher F1-Measure than related approaches. Moreover, the plugin reduces and simplifies the manual effort required when configuring and using static analysis tools.

UNav-Sim: A Visually Realistic Underwater Robotics Simulator and Synthetic Data-Generation Framework - Amer, Abdelhakim; Álvarez-Tuñón, Olaya; Uğurlu, Halil İbrahim; Le Fevre Sejersen, Jonas; Brodskiy, Yury; Kayacan, Erdal (2023 21st International Conference on Advanced Robotics (ICAR))

Singen auf TikTok und Co. Sind Gesangspraktiken in (post)digitaler Kultur (k)ein Thema für die Musikpädagogik? - Godau, Marc (Stimme, Medien, Umwelt. Kinder- und Jugendstimme)

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

„Ich find’s aber trotzdem unfair.“. Argumentausbau in argumentativen Gesprächen und Briefen von Schüler*innen - Rezat, Sara; Grundler, Elke; Schmölzer-Eibinger, Sabine (Textprozeduren in Spannungsfeldern)

Erklärvideos. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch)

Textprozeduren in Spannungsfeldern